2021
DOI: 10.4018/ijmmme.2021040103
|View full text |Cite
|
Sign up to set email alerts
|

Formability of AA7075 Sheet in Single Point Incremental Forming

Abstract: This article presents formability analysis of aluminium alloy 7075 thin sheets in single point incremental forming (SPIF) through prediction of forming limit curve (FLC) and maximum formable wall angle. Deformation instability method based on tool-sheet contact and non-contact zones in incremental forming was used for the prediction of limit strains for plane strain and equi-biaxial stretching strain path. FLC of the material was also determined experimentally, after measuring limit strains for deformed sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Parametric study and multi-objective optimization of formability of aluminum alloy sheet in SPIF were investigated by Maji and Kumar. 13 Theoretically predicted forming limit curves for different aluminum alloy sheets (AA6061, AA5083, AA7075) using deformation instability method [14][15][16] were observed to be higher compared to the experimental values predicted by incremental sheet forming tests as reported by Do et al 17 Maji et al 18 also studied the effect of friction stir welding on formability in SPIF process for AA5083 sheet and lower formability of the welded sheet was observed compared to the base sheet material. Asghar et al 19 developed a mathematical model based on mechanics to improve the dimensional accuracy in SPIF process for sheet metal deformed parts.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Parametric study and multi-objective optimization of formability of aluminum alloy sheet in SPIF were investigated by Maji and Kumar. 13 Theoretically predicted forming limit curves for different aluminum alloy sheets (AA6061, AA5083, AA7075) using deformation instability method [14][15][16] were observed to be higher compared to the experimental values predicted by incremental sheet forming tests as reported by Do et al 17 Maji et al 18 also studied the effect of friction stir welding on formability in SPIF process for AA5083 sheet and lower formability of the welded sheet was observed compared to the base sheet material. Asghar et al 19 developed a mathematical model based on mechanics to improve the dimensional accuracy in SPIF process for sheet metal deformed parts.…”
Section: Introductionmentioning
confidence: 81%
“…The detail methods for calculation of forming and supporting forces in SPIF of monolithic sheets have been reported by authors. 15,16 The friction and shear effect along the circumferential direction, elastic deformation in the NZ due to tool movement, and material anisotropy are neglected in this method.…”
Section: Deformation Instability Methodsmentioning
confidence: 99%
“…Yoganjaneyulu et al [25] presented that the forming limit of the topmost sheet was maximum in the case of multi-sheet incremental forming of a titanium sheet, and it decreased towards the bottom sheets. Kumar and Maji [26] presented the estimations of the forming limit of aluminium alloy sheets during SPIF via the deformation instability method (Figure 3). Fig.…”
Section: Forming Limit Curvesmentioning
confidence: 99%
“…Yoganjaneyulu et al [145] showed that the forming limit of the uppermost sheet was highest in the case of multi-sheet incremental forming of a titanium sheet, and it decreased towards the bottom sheets. Kumar and Maji [146] showed predictions of the forming limit of aluminium alloy sheets in SPIF by the deformation instability approach (Figure 11a-c). Su et al [78] determined suitable process parameters to maximise the forming limit in SPIF of aluminium alloy sheets using numerical simulations and experiments.…”
Section: Forming Limit Curvesmentioning
confidence: 99%
“…These materials are prone to adhesive wear and galling. Currently, assurance of the correct friction conditions is mainly done through novel lubrication, the optimisation of the forming strategy, and modification of the tool surface (Table 2) [146][147][148][149][150][151].…”
Section: Friction and Lubrication In Spif 81 Friction Conditionsmentioning
confidence: 99%